Web services security development and architecture theoretical and practical issues - Gutierrez, Carlos; Fernández-Medina, Eduardo; Piattini, Mario 1966- (Premier reference source, 2010)
"This book's main objective is to present some of the key approaches, research lines, and challenges that exist in the field of security in SOA systems" - Provided by publisher